PHENOL TOLERANCE AND DEGRADATION PROFILE OF NOVEL EDIBLE MUSHROOM HYPSIZYGUS ULMARIUS IN LIGNINOLYTIC AND NON-LIGNINOLYTIC MEDIA - R. RANJINI,; T. PADMAVATHI, (International Journal of Pharma and Bio Sciences, 2012)
Phenol tolerance and degradation using spent mycelium substrate of Hypsizygus ulmarius showed that ligninolytic media with carbon or nitrogen limitation gave highest growth (26.27sq.cm), while limitation of both nutrients reduced it to 8.1sq.cm. 7.68sq.cm was seen in non-ligninolytic media; simultaneous nutrient increase gave 1.16sq.cm. Tolerance to phenol was best in ligninolytic media with carbon or nitrogen limitation. When phenol was introduced, growth decreased. Phenol increase from 200 to 400mg/L caused further decrease in nitrogen-optimum(7.03 to 2.35 sq.cm) and deficient(6.33 to 1.23 sq.cm) media, while nitrogen-deprived (2.48 to 5.52 sq.cm) media showed increase. Tolerance to higher phenol concentrations was accentuated by severe nitrogen limitation. Correlation of 0.99 between ligninolytic and non-ligninolytic media showed growth pattern similar irrespective of nutrient levels. Nitrogen reduction achieved 63% degradation from 200-800mg/L phenol, while carbon limitation gave 55.75%. Negligible degradation in non-ligninolytic condition. At lower phenol concentration, nitrogen limitation beneficial; for higher concentrations, carbon limitation helped.